2003
DOI: 10.1111/1469-7610.00184
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent twins discordant for major depressive disorder: shared familial liability to externalizing and other internalizing disorders

Abstract: These results support a shared familial liability between MDD and other internalizing disorders and between MDD and externalizing disorders in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…For example, it could be that the affective disorders alone are responsible for the connection between family history of psychopathology and recurrence of depression; alternatively it could be that anxiety disorders or substance use disorders, for example, are also related to recurrence. In addition, studies of this type must be performed on genetically informative samples in order to account for the high comorbidity and familial liability between depression and other forms of psychopathology (Burcusa, Iacono, & McGue, 2003;Kendler et al, 1995;Kessler et al, 1996;Krueger, 1999).…”
Section: Family History Of Psychopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it could be that the affective disorders alone are responsible for the connection between family history of psychopathology and recurrence of depression; alternatively it could be that anxiety disorders or substance use disorders, for example, are also related to recurrence. In addition, studies of this type must be performed on genetically informative samples in order to account for the high comorbidity and familial liability between depression and other forms of psychopathology (Burcusa, Iacono, & McGue, 2003;Kendler et al, 1995;Kessler et al, 1996;Krueger, 1999).…”
Section: Family History Of Psychopathologymentioning
confidence: 99%
“…For example, it could be that the affective disorders alone are responsible for the connection between family history of psychopathology and recurrence of depression; alternatively it could be that anxiety disorders or substance use disorders, for example, are also related to recurrence. In addition, studies of this type must be performed on genetically informative samples in order to account for the high comorbidity and familial liability between depression and other forms of psychopathology (Burcusa, Iacono, & McGue, 2003;Kendler et al, 1995;Kessler et al, 1996;Krueger, 1999).There are different mechanisms through which a family history of psychopathology could be related to recurrence of depression. The results of family studies suggest that the familial transmission of recurrent depression is even stronger than the familial transmission of depression in general (Klein, Lewinsohn, Rohde, Seeley, & Durbin, 2002;Zubenko et al, 2001), particularly if it is early-onset recurrent depression (Moldin, Reich, & Rice, 1991).…”
mentioning
confidence: 99%
“…Since MZ and DZ twins did not differ in their prevalence rates of CP or any of the COPCs or chronic pain conditions, all study analyses were conducted with MZ and DZ pairs combined. Combining MZ and DZ twins in the absence of zygosity differences is common in discordant twin studies (24, 25). We followed a multiple step analytic procedure to examine the association of CP and COPCs and determine if evidence of familial confounding exists (26).…”
Section: Methodsmentioning
confidence: 99%
“…Biometric models developed with our 17-year-old twins indicate that conduct disorder, antisocial personality disorder, adolescent/adult antisocial behavior (AAB; a syndrome characterized by the presence of ASPD antisocial behaviors with onset after age 15), nicotine dependence, alcohol use disorders, illicit drug use disorders, and the personality trait constraint all load strongly on this latent factor (Burcusa et al, 2003;Hicks et al, 2004;McGue et al, 2006). In the parents of MTFS twins, who are over the age of maximal risk for the development of externalizing psychopathology, direct comparisons of categorical and dimensional models of the latent externalizing liability demonstrated that the liability is continuous and graded, as opposed to delineating discrete categories of psychopathology in nature .…”
Section: Behavioral Disinhibition In Late Adolescence and Early Adultmentioning
confidence: 99%
“…Our assessment protocol covers negative emotionality, including associated personality traits, major depression, and anxiety disorders. Although our work has begun to explore the relationship between the development of SUDs, negative emotion (Elkins et al, 2006, and internalizing psychopathology (Burcusa et al, 2003;Herndon & Iacono, 2005;King et al, 2004;Marmorstein & Iacono, 2003, 2004, we hope to expand our efforts in this important domain.…”
Section: Future Directionsmentioning
confidence: 99%